Dynamic communication and perception of cyber risk: Evidence from big data in media. (September 2021) - Xu, Wei; Murphy, Finbarr; Xu, Xian; Xing, Wenpeng
Abstract: Cyber risk is consistently viewed as a threat to the proper function of commercial and societal activity. Regardless of whether this risk is real or perceived, understanding how societal communication and perception of it change over time has important implications for both regulatory authorities and insurers. This contribution analyzes Chinese media news over the years 2009–2018 to identify the dynamics of cyber risk sources and associated societal assessment. Taking the psychometric paradigm as its point of departure and applying combination of computational and statistical methods, we identify 34 sources of cyber risk. The actions of government turn out to have a significant impact on public attention to the different sources of cyber risk, an influence that has been neglected in past research. The dynamics of societal aversion against most cyber risk sources are found to present inverted-U shapes. Adaptation and learning effects are found to explain this dynamic. Another finding is that news sentiment has a strong correlation with cyber risk perception, an insight of importance for regulators and insurers. Highlights: Online financial fraud and phone taps are the most concerned cyber risks in China. Chinese public attention to negative cyber risk sources is lower in recent years. Government action affects the distribution of public attention to cyber risk sources. Societal assessment on most cyber risk sources has an inverted-U shape over years. Societal cyber risk perception relates more to news sentiment than to news amount.